PERGESERAN POLA INTERAKSI WARUNG KOPI PADA MASYARAKAT ACEH BARAT - Mursyidin Mursyidin (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
This article intends to examine how changes in the patterns of social interaction in coffee shops occur, how they change and what factors cause change. Data were obtained from the results of observations and literature studies which were then analyzed using a qualitative approach with descriptive analytical methods. The results of this study indicate that the development of digital technology, globalization and cultural contact that occur through digital media has influenced the patterns of interaction between Acehnese people in coffee shops, especially in young people. The interaction in the coffee shop changes from an interaction / verbal communication model to a virtual interaction. Besides that the function of the coffee shop has also changed, now the coffee shop is no longer a space for discussion and interaction but is a symbol of the lifestyle of young people and at the same time a